Assesment of Damage in Juvenile Idiopathic Arthritis: Single Center Experience - Sevda Asadova; Ayşenur Paç Kısaarslan; Sümeyra Özdemir Çiçek; Nihal Şahin; Sema Nur Taşkın; Şeyda Doğantan; Muammer Hakan Poyrazoğlu (The Journal of Pediatric Academy, 2022)
Introduction:It is essential to evaluate the activation and the articular and extra-articular damage during the Juvenile Idiopathic Arthritis(JIA) disease course.